Optimalisasi Pembangunan Sektor Pertanian Indonesia dengan Menggunakan Sharia Agraria Manajement Organization (SAMO) - Nina Sakinah; Eka Purwanti; Siti Jamilah (Perisai : Islamic Banking and Finance Journal, 2018)
Indonesia is an agrarian country. Many Indonesians work as farmers. The agricultural sector has a great function in maintaining national food security, especially in maintaining the welfare of farmers. Interim data in 2013 show that the agricultural sector is in second position in contributing to GDP. With the existing data then the farmers should be able to live prosperous. But in reality farmers in Indonesia have problems that cause their quality of life is still far from the word worthy, such as low income and productivity, difficulties in credit applications, low education and irrigation systems that have not been optimal. Judging from the existing problems it is necessary to establish a management system that can overcome them. The purpose of this research is to optimize the potential of agricultural sector in Indonesia by using Sharia Agraria Management Organization (SAMO) by synergizing Baitul Mal Wa Tamwil (BMT) with Local Government and Central Government. This research was conducted by Meta Analysis method, based on observation and literature study, the authors conclude that with the existence of SAMO, farmers can improve their standard of living, increased productivity, and easy in the application of farming credit. It is expected that with this system can maintain the quality of the community environment and achieve the implementation of sustainable development.